(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The purpose of this study was to examine the changes in incidence and prevalence of cataract during the 10-year period between 2007-2016 among children who had been registered in the Health Care of Ukraine. In Ukraine, the cataract prevalence was among children above the average as compared to other countries in Europe. The cataract prevalence decreased in most regions (except Poltava region where it increased 2.2 times and Kherson region where in increased by 6.1%). The worst situation of pediatric cataract incidence was in Rivne region, the best one was in Poltava region. Over 10 years, the cataract incidence did not change in seven regions and increased in Sumy and Kherson regions. The cataract incidence decreased by 75% in Cherkasy and Zaporizhia regions. Dynamic of pediatric cataract showed the worst situation in the Kherson region and the best one in Zaporizhia region. Over the period 2007-2016, there was a decrease in prevalence and incidence of cataract in all age groups of children. The cataract incidence in rural population of children prevailed over children in the urban area, especially it was noticeable in 2015. There was a positive dynamics, especially in the cataract prevalence in children from the urban area. The incidence of cataract in adolescent girls was less than in boys, but there was a positive dynamics regarding the cataract prevalence among the teenagers, except the cataract incidence in boys which did not change. The cataract incidence increased with age, the highest level were recorded in the adult population (18 and older). Among the children population, the incidence reached the highest rates in adolescence.